The policy of granting scientific grants in Russia and its prospects - N. A. Bobrova (Правоприменение, 2022)
Modern criteria for assessing scientific activity, established in 2013, are considered. The shortcomings of these criteria, which the author of this article, together with another professor, tried to recognize as invalid and not subject to application due to their contradiction with Russian legislation and national interests, are emphasized. The requirements for applicants for grants of the Russian Science Foundation are considered (RSF), which, after merging with the Russian Foundation for Basic Research (RFBR), became the only federal scientific foundation. The first results of the merger of the two funds are analyzed. It is shown that this had a negative impact on the humanities, including legal sciences. The Resolution of the Government of the Russian Federation dated March 19, 2022 No. 414 "On some issues of applying the requirements and target values of indicators related to publication activity" is analyzed. The resolution was adopted in response to the sanctions of unfriendly states, as well as a reaction to open letters from the public about the immediate exclusion from all regulations of the requirement to publish in journals from commercial indices. The resolution has the character of a moratorium on the application of requirements for the availability of publications in scientific journals indexed in international databases. Proposals are being made on the development of domestic criteria for publication activity.